(untitled) (Ciudades, 2017)
The Management Plan fro the Old City of Salamanca, assigned by the Castilla y León Government, is the result of the current UNESCO directives oriented to introduce new management tools fitted for any case. However practically does not exist experience. In this context the plan guides its main scope, the efficiency in the “outstanding universal value” protection and revalorization for justifying the Salamanca inclusion in the World List, with an innovative development of the “historical urban landscape” concept. This is focused from three perspectives: the territory, the inner city landscape and the intangible landscape. This paper explains the elements of the proposal –now involved in its approval process-, the Management Plan and the lan for the Urban Conservation Area included in it. But, over all, this paper shows an open model for understanding the urban heritage components, model which is in the basis of the improvement principles applied.